Organization and implementation of a cardio-oncology program - Manuela Fiuza (Revista Portuguesa de Cardiologia (English Edition), 2016)
Considerable advances in cancer therapies in recent decades have reshaped the prognosis of cancer patients. There are now estimated to be over 20 million cancer survivors in the USA and Europe, numbers unimaginable a few years ago. However, this increase in survival, along with the aging of the patient population, has been accompanied by a rise in adverse cardiovascular effects, particularly when there is a previous history of heart disease. The incidence of cardiotoxicity continues to grow, which can compromise the effectiveness of cancer therapy. Cardiotoxicity associated with conventional therapies, especially anthracyclines and radiation, is well known, and usually leads to left ventricular dysfunction. However, heart failure represents only a fraction of the cardiotoxicity associated with newer therapies, which have diverse cardiovascular effects. There are few guidelines for early detection, prevention and treatment of cardiotoxicity of cancer treatments, and no well-established tools for screening these patients. Echocardiography is the method of choice for assessment of patients before, during and after cancer treatment.It therefore makes sense to adopt a multidisciplinary approach to these patients, involving cardiologists, oncologists and radiotherapists, collaborating in the development of new training modules, and performing clinical and translational research in a cardio-oncology program. Cardio-oncology is a new frontier in medicine and has emerged as a new medical subspecialty that concentrates knowledge, understanding, training and treatment of cardiovascular comorbidities, risks and complications in patients with cancer in a comprehensive approach to the patient rather than to the disease. Resumo: A taxa de sobrevivência dos doentes (dts) com cancro aumentou consideravelmente nas últimas décadas, havendo atualmente mais de 20 milhões de sobreviventes nos EUA e na Europa, números inimagináveis até há poucos anos. Para tal, muito contribuiu o aparecimento de novos fármacos (terapêuticas biológicas).No entanto, estes benefícios na sobrevivência e o envelhecimento da população foram acompanhados de um aumento da taxa de efeitos adversos cardiovasculares, sobretudo se já havia doença cardíaca prévia. De facto, a incidência de cardiotoxicidade (CTX) tem sido continuamente mais evidente, comprometendo a eficácia das terapêuticas oncológicas (TO). São conhecidos os efeitos adversos cardíacos das TO tradicionais (antraciclinas e radioterapia torácica), como a insuficiência cardíaca. Contudo, esta representa apenas uma fração das manifestações de CTX, pois muitas das novas terapêuticas têm efeitos cardiovasculares diversos. As orientações clínicas existentes para fazer a deteção precoce, a prevenção e o tratamento da CTX dos tratamentos oncológicos, não abrangem todas as manifestações de CTX e ainda são poucas as ferramentas para a avaliação destes dts. A ecocardiografia é atualmente o método de escolha para avaliar os dts nas fases pré, durante e após a TO.Dada a dimensão e relevância desta questão, faz todo o sentido falar de cardio-oncologia, uma nova subespecialidade médica. O número crescente de dts oncológicos com problemas cardíacos implica uma abordagem que deve ser partilhada entre cardiologistas, oncologistas e radioterapeutas.Esta nova área do conhecimento médico deve também incluir uma componente formativa clínica, sendo também desejável a implementação de projetos de investigação clínicos e transacionais. Keywords: Cancer, Cardiotoxicity, Cardio-oncology, Chemotherapy, Radiation, Heart failure, Palavras-chave: Cancro, Cardiotoxicidade, Cardio-oncologia, Quimioterapia, Radioterapia, Insuficiência cardíaca